Pengaruh cash holding, profitabilitas dan financial leverage terhadap income smoothing - Umi Kholifah; Ardi Paminto; Muhammad Amin Kadafi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This study aims to predict the probability of the effect of variable cash holding, profitability, and financial leverage to the use of income smoothing on food and beverages industry listed on the Stock Exchange in 2011-2015. The population of this study were 17 industrial food and beverages listed on the Indonesia Stock Exchange. The sampling method used is purposive sampling method, in order to obtain 14 industrial samples for 5 years of observation (2011-2015) with 70 observations. Data were obtained from financial statements that have been published and downloaded from the website of Indonesia Stock Exchange is www.idx.co.id. Data analysis technique used is multiple linear regression analysis. The results of this study indicate that the cash holding and profitability has a significant positive effect on  income  smoothing.  While  financial  leverage  has  a  significant  negative  effect  on  the  income smoothing.Keywords: cash holding, return on asset, debt to total asset, income smoothing.